Study of Anti-Cancer Property of Olive Oil Against DMBA Induced Breast Cancer in Rats - Yasmin, Farhat; Deen, Sidhnath Prasad Yadav; Kareem, Shabana; Maiti, Tushar Kanti; Niraj, Pintoo Kumar; Ali, Mohammad (Archives of Clinical and Biomedical Research, 2026)
Background: The present study has been designed to evaluate the tumor regression properties of olive oil in a rat model with DMBA-induced breast tumors. Methods: Female Charles Foster rats were given DMBA orally (20 mg/mL diluted in olive oil). The rats received oral treatment with olive oil (2000mg/ kg) for four weeks after developing breast tumors. Results: In the present investigation after administration of olive oil for 4 weeks reduction in tumor size was observed from 1.2 cm to 0.6 cm associated with a significant decrease in LPO level. The decreased serum tnf alpha level was also observed as compared to DMBA treated. On the other hand, therapeutic response of olive was also observed in histopathological study. Apoptosis, reduced mitoses and inflammatory infiltration may reflect the anticancer potential of olive oil. A decrease in level of estradiol was observed as compared to DMBA treated, however no changes in serum progesterone level was observed. Conclusion: Based on the complete study, it can be concluded that olive oil has anti-proliferative properties by slowing the growth of breast cancers in rat models.